A relação entre os conceitos de alienação e fetichismo da mercadoria no pensamento de Karl Marx - Lima, Gerson Lucas Padilha de (2015)
The purpose of this research is to analyze the relation of similarity, complementarity and difference between the concepts of alienation and commodity fetishism, as were themed by the thought of Karl Marx. Marx makes a critique concerning the forms of being alienated and fetishized of capitalist society; of Politics, Economics, Philosophy, Science, Art, Morals etc., in analogy with Feuerbach's critique of religious alienation. In this perspective, in the first chapter we discussed the Feuerbachian criticism to the structure of religious alienation, and then, we investigate, in a comparative way, the manner in which Marx uses it to elaborate the critique of modern political society, which found in the philosophy speculative Hegelian the deeper and systematic explanation of its legal and political principles as such. In the second chapter, we analyze how Marx understood the phenomena social, materials and economical alienated of the capitalist society, which is based on alienated labor from the meeting with the thought of bourgeois political economy, conceived in analogy with the Feuerbachian criticism about the religion. Lastly, in the third chapter, we discussed the constitution of the human condition through the active and conscious relation between man and nature, mediated by the living labor subsumed to the principle of capital. Thus, we investigate the relation of alienation with the concept of commodity fetishism by the advance of Marxian inquiry about the criticism of political economy.